2007
DOI: 10.1271/bbb.60697
|View full text |Cite
|
Sign up to set email alerts
|

A New Proteasome Inhibitor, TP-110, Induces Apoptosis in Human Prostate Cancer PC-3 Cells

Abstract: Proteasome inhibitors are useful in the treatment of cancer. Recently, we found a new proteasome inhibitor, TP-110, derived from tyropeptin A produced by Kitasatospora sp. Here we report that TP-110 induces apoptosis in human prostate cancer PC-3 cells. TP-110 showed strong cytotoxicity to PC-3 cells (IC(50)=0.05 muM). It increased the number of cells in the G(2)-M phase and increased the accumulated amounts of the p21 and p27 proteins, which are negative regulators of cell cycle progression. Furthermore, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Supporting previous work showing that the impairment of proteasome activity induces apoptotic tumor cell death and cell cycle arrest at G 2 /M phase [4] , we prove in this study that inhibition of the proteasome by MG-132 decreases cell proliferation, induced cell death and G 2 /M arrest and activates autophagy in SHG-44 glioma cells. Furthermore, we found that 6.0 µmol/L MG-132 effectively inhibited proteasome activity and induced cell death and cell cycle arrest in SHG- www.nature.com/aps Ge PF et al Acta Pharmacologica Sinica npg 44 glioma cells, which was consistent with a previous report [5] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Supporting previous work showing that the impairment of proteasome activity induces apoptotic tumor cell death and cell cycle arrest at G 2 /M phase [4] , we prove in this study that inhibition of the proteasome by MG-132 decreases cell proliferation, induced cell death and G 2 /M arrest and activates autophagy in SHG-44 glioma cells. Furthermore, we found that 6.0 µmol/L MG-132 effectively inhibited proteasome activity and induced cell death and cell cycle arrest in SHG- www.nature.com/aps Ge PF et al Acta Pharmacologica Sinica npg 44 glioma cells, which was consistent with a previous report [5] .…”
Section: Discussionsupporting
confidence: 91%
“…The proteasome is involved not only in protein degradation, but also in cellular differentiation, antigen presentation and cell cycle modulation [2] . Therefore, inhibition of proteasome activity has become a new chemotherapy strategy and many chemicals and natural compounds have proven to be effective at inducing tumor cell death by inhibiting proteasome activity [3][4][5][6] . Autophagy, as part of the lysosomal system, is an evolutionarily conserved cellular strategy to engulf and degrade long-lived cytosolic proteins and organelles to provide substrates for energy metabolism and to recycle amino acids, fatty acids, and nucleotides for the biosynthetic needs of cells [7] .…”
Section: Introductionmentioning
confidence: 99%
“…1) strongly inhibits the growth of various human cell lines and induces apoptosis in their cells. 12) In order to strengthen its therapeutic effects, we established RPMI-8226/TP-110 cells and elucidated their resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…11) TP-110 strongly inhibits the growth of human tumor cells and induces apoptosis. 12) One of the mechanisms of apoptosis induction by TP-110 is down-regulation of inhibitors of apoptosis proteins (IAPs) in multiple myeloma cells. 13) A loss of anti-tumor efficacy responsible for drugresistance in cells is known in cancer chemotherapy.…”
mentioning
confidence: 99%
“…Therefore, inhibition of proteasome activity has emerged as a new chemotherapy strategy for malignant tumors. Although studies have shown that inhibition of proteasome activity could inhibit cellular proliferation in several tumor cell lines including melanoma, prostate cancer and glioma cells [3][4][5][6] , its underlying mechanism is not fully understood. The proteasome inhibitor bortezomib has been authorized by the US Food and Drug Administration to enter clinical trials, but it is used mainly in the leukemia field.…”
Section: Introductionmentioning
confidence: 99%